2019
DOI: 10.24198/jbm.v20i2.287
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Business Education on Entrepreneurial Intention With Feasibility and Entrepreneurial Self-Efficacy as Intervening Variables

Abstract: This study aims to examine the effect of business education on entrepreneurial intention with feasibility and entrepreneurial self-efficacy as the intervening variables. This study was conducted on students of Business study programs, Faculty of Administrative Sciences, Universitas Brawijaya (FIA UB). The number of samples used in this study was 321 students using proportionate stratified random sampling. The questionnaire was used to collect data, and Partial Least Square (PLS) was used for the analysis. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
1
3
0
2
Order By: Relevance
“…These results are in accordance with previous research, which showed that self-efficacy and student learning motivation, both partially and simultaneously, had an effect on learning outcomes (Monika & Adman, 2017). Selfefficacy determines how a person feels, thinks, motivates himself and behaves (Deliana et al, 2019). It has been explained that mathematics learning achievement is a change in behaviour that is obtained through the experience of students from various problem-solving activities, so that the concept of mathematical theory is obtained well (Sudjana, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…These results are in accordance with previous research, which showed that self-efficacy and student learning motivation, both partially and simultaneously, had an effect on learning outcomes (Monika & Adman, 2017). Selfefficacy determines how a person feels, thinks, motivates himself and behaves (Deliana et al, 2019). It has been explained that mathematics learning achievement is a change in behaviour that is obtained through the experience of students from various problem-solving activities, so that the concept of mathematical theory is obtained well (Sudjana, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…A direct association between risk-taking propensity and intention to new business venturing seems logical, but the present study suggested an insignificant relationship between these variables. This opens a new frontier in entrepreneurial research that identifies antecedents that mediates or moderate risk-taking propensity into new business venturing as risk-taking behaviour has been identified as an important behavioural imperative for entrepreneurs in a number of studies (Cooper et al, 1988; Deliana et al, 2019; Palich & Bagby, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Sejalan dengan hal tersebut, temuan kajian Deliana et al, (2019) serta Daneshjoovash dan Hosseini, (2019) menunjukkan bahwa pendidikan kewirausahaan akan mengembangkan generasi Z untuk berperilaku wirausaha dan menjawab tantangan masa depan. Efikasi diri berkontribusi dalam membentuk minat generasi Z untuk mempercayai berbagai hal dalam kehidupannya, termasuk dalam berwirausaha.…”
Section: Pembahasanunclassified